(untitled) (Al-Academy, 2017)
It boils down search is marked by (employing technology in the establishment of globalization in the Film Art), and walk parallel plan between the technical and artistic movements and the impact of globalization on the final performed in the film Film of innovations and technology and rapid capital that provided the filmmakers and Kartalatha which focused entirely in the embodiment of the idea and published in the service around the world. And distributes research on four chapters first chapter dealt with the methodological framework of the research, which included research problem marked by the following question: (What are the modalities to employ technology in the establishment of globalization in the Film Art?) And the importance of research and its objectives and the limits of research and definition of key terms that came in the search. The second chapter, a theoretical framework and previous studies. And distributes the theoretical framework of the three sections, taking the first section includes a technical impact on the cinematic art, the extrapolation of the historic march of the evolution of technology (picture elements) in the audio-visual scope of supply and development techniques. And taking second section the concept of globalization and its relationship with technology in the film Alcinmaia.oma third section junk technology and its role in the delivery of the American film to the role of global supply in the establishment of globalization, the role of these technologies in the embodiment of contents and ideas presented in the text through her portrayal of movies to these processors and different levels. In the third chapter, which has been allocated to research procedures, which included research methodology, and appointed intentionality included not: (c Matrix 1 The Matrix). As well as research and analysis unit and its tool and analysis steps society then, Neshat sample analysis. Then the fourth quarter, Neshat sample analysis. The fifth chapter Vahtoy results. As well as the conclusions reached by the researcher. It must Research of this type that contains the sources supports the scientific research process